Positive electrode material for lithium-sulfur battery and lithium-sulfur battery comprising same
By using sulfur-carbon composite materials in lithium-sulfur batteries to coat the crosslinked products of amphiphilic cashew phenol derivatives, the problem of lithium polysulfide dissolution is solved, the discharge capacity and capacity retention rate of lithium-sulfur batteries are improved, and the discharge capacity and capacity retention rate of lithium-sulfur batteries are enhanced. Battery stability and safety.
Patent Information
- Application Number
- CN202380045114.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-31
- Filing Date
- 2023-07-24
- Publication Date
- 2025-01-03
AI Technical Summary
Due to the insulating properties of sulfur materials in lithium-sulfur batteries, electrons are difficult to transfer, and lithium polysulfide dissolves during the charging/discharge cycle, resulting in a rapid decrease in battery capacity and an unstable interface forming, which is called the 'shuttle effect'.
Using sulfur-carbon composite materials, the cross-linked product of amphiphilic cashew phenol derivatives is coated on the porous carbonaceous substrate to form a fully or partially surface-coated structure to inhibit the dissolution of lithium polysulfide and improve the positive electrode. Conductivity and structural stability.
It effectively inhibits the dissolution of lithium polysulfide, improves the discharge capacity and capacity retention rate of lithium sulfur batteries, reduces the volume expansion of the positive electrode, and enhances the safety and cycle stability of the battery.
Smart Images

Figure CN119256401A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a positive electrode material for a lithium-sulfur battery and a lithium-sulfur battery comprising the positive electrode material.
[0002] This application claims priority to Korean Patent Application No. 10-2022-0110405 filed in Korea on August 31, 2022, the disclosure of which is incorporated herein by reference. Background Art
[0003] Lithium-sulfur batteries are battery systems that use sulfur-sulfur (SS) bonds as positive electrode active materials and lithium metal as negative electrode active materials. Sulfur, the main component of the positive electrode active material, has advantages in that it is globally abundant, non-toxic, and has a low atomic weight.
[0004] As the application range of secondary batteries expands to electric vehicles (EVs), energy storage systems (ESS), etc., the technology of lithium-sulfur batteries that can achieve a theoretically higher energy storage density per unit weight (~2,500 Wh / kg) compared with lithium-ion secondary batteries with a relatively lower energy storage density per unit weight (~250 Wh / kg) has come into focus.
[0005] In a lithium-sulfur battery, during discharge, while lithium as a negative electrode active material provides electrons and is ionized and oxidized to lithium cations, the sulfur-based material as a positive electrode active material accepts electrons and is reduced. Here, the SS bond accepts two electrons through the reduction of the sulfur-based material and is converted into a sulfur anion form. The lithium cations generated by the oxidation of lithium are transferred to the positive electrode through the electrolyte and combined with the sulfur anions generated by the reduction of the sulfur-based compound to form a salt. In particular, the sulfur before discharge has a cyclic S8 structure, which is converted into lithium polysulfide (Li2S x ) and is completely reduced to form lithium sulfide (Li2S).
[0006] Therefore, since sulfur used for the positive electrode active material is an insulator, there are problems to be solved in that electrons generated by electrochemical reactions are difficult to transfer and lithium polysulfide (Li2S) is generated during the charge / discharge cycle. x ) dissolution, resulting in a rapid decrease in battery capacity.
[0007] For example, sulfur used in the positive electrode forms lithium polysulfide while being reduced during discharge, and the formed lithium polysulfide dissolves in the ether liquid electrolyte and dissolves from the positive electrode. The dissolved lithium polysulfide passes through the separator and reaches the negative electrode, causing a side reaction with metallic lithium, thereby forming an unstable interface. This leads to the loss of sulfur as the positive electrode active material, and this series of processes is called the "shuttle effect".
[0008] In these cases, techniques are needed to suppress the loss of battery energy density caused by this shuttling effect. Summary of the invention
[0009] Technical issues
[0010] The present invention aims to solve the problems of the prior art, and therefore the present invention aims to provide a sulfur-carbon composite material and a method for preparing the sulfur-carbon composite material, wherein the sulfur-carbon composite material is fully or partially coated with a polymer on the surface, thereby inhibiting the dissolution of lithium polysulfide from the positive electrode of a lithium-sulfur battery.
[0011] In particular, the present invention aims to provide a lithium-sulfur battery having excellent discharge capacity and capacity retention rate by suppressing the shuttle effect through the coating structure of the sulfur-carbon composite material and suppressing the volume expansion of the positive electrode.
[0012] Technical Solution
[0013] In one aspect of the present invention, there is provided a sulfur-carbon composite material according to any one of the following embodiments.
[0014] According to a first embodiment of the present invention, there is provided a sulfur-carbon composite material, the sulfur-carbon composite material comprising:
[0015] a porous carbonaceous substrate; and
[0016] a sulfur-containing compound contained in at least one of an outer surface of the porous carbonaceous substrate and an inner surface of the pores of the porous carbonaceous substrate, and
[0017] The sulfur-carbon composite material is entirely or partially coated on the surface with a cross-linked product of an amphiphilic cardanol derivative represented by the following chemical formula 1:
[0018] [Chemical formula 1]
[0019]
[0020] wherein R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl; and
[0021] R2 represents at least one selected from the group consisting of a C1-C10 alkyl group, a C2-C10 alkenyl group, and a C2-C10 alkynyl group, and has a structure substituted with at least one anionic functional group.
[0022] According to a second embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in the first embodiment, wherein the surface of the sulfur-carbon composite material may exhibit a zeta potential satisfying the following formula 1:
[0023] [Formula 1]
[0024] -60 mV≤ζ≤0 mV
[0025] According to a third embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in the first or second embodiment, wherein at least one of R1 and R2 in the amphiphilic cardanol derivative may have a structure containing at least one unsaturated bond between carbon atoms.
[0026] According to a fourth embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in any one of the first to third embodiments, wherein R2 may represent -(CH x ) n Q (wherein x=0, 1 or 2, n is an integer of 1-10, and Q is an anionic functional group).
[0027] According to a fifth embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in any one of the first to fourth embodiments, wherein the anionic functional group may comprise at least one functional group selected from the following: - 、-SO3 - 、-COO - 、-SO4 2- and its conjugate acid.
[0028] According to a sixth embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in any one of the first to fifth embodiments, wherein the anionic functional group contained in R2 may further contain at least one of an alkali metal ion and an alkaline earth metal ion as a cation.
[0029] According to a seventh embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in any one of the first to sixth embodiments, wherein the degree of crosslinking of the crosslinked product of the amphiphilic cardanol derivative as determined by the following formula 2 may be 15%-45%:
[0030] [Formula 2]
[0031] Cross-linking degree (%) = (carbon unsaturation degree of the cross-linked product of the amphiphilic cardanol derivative / carbon unsaturation degree of the amphiphilic cardanol derivative) × 100
[0032] According to an eighth embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in any one of the first to seventh embodiments, wherein R1 in the amphiphilic cardanol derivative may have at least one structure selected from the following Chemical Formulas 2 to 5:
[0033] [Chemical formula 2]
[0034]
[0035] [Chemical formula 3]
[0036]
[0037] [Chemical formula 4]
[0038]
[0039] [Chemical formula 5]
[0040]
[0041] According to a ninth embodiment of the present invention, a sulfur-carbon composite material as defined in any one of the first to eighth embodiments is provided, wherein the amphiphilic cardanol derivative may contain 1-10 parts by weight of a structure in which R1 represents chemical formula 2, 40-70 parts by weight of a structure in which R1 represents chemical formula 3, 5-25 parts by weight of a structure in which R1 represents chemical formula 4, and 25-40 parts by weight of a structure in which R1 represents chemical formula 5.
[0042] According to a tenth embodiment of the present invention, a sulfur-carbon composite material as defined in any one of the first to ninth embodiments is provided, wherein the porous carbonaceous substrate may comprise: carbon black, carbon fiber, carbon nanotube (CNT), graphene, graphene oxide (GO), reduced graphene oxide (rGO), graphite, graphite nanofiber (GNF), carbon nanofiber (CNF), activated carbon fiber (ACF), natural graphite, artificial graphite, expanded graphite, activated carbon, fullerene or two or more thereof.
[0043] According to an eleventh embodiment of the present invention, there is provided a sulfur-carbon composite material as defined in any one of the first to tenth embodiments, wherein the sulfur-containing compound may include inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 2≤x≤8), a disulfide compound or a mixture of two or more thereof.
[0044] According to a twelfth embodiment of the present invention, there is provided a sulfur-carbon composite material as described in any one of the first to eleventh embodiments, wherein the total content of the cross-linked product of the amphiphilic cardanol derivative may be 0.1-10 wt % based on the total weight of the sulfur-carbon composite material.
[0045] According to a thirteenth embodiment of the present invention, there is provided a sulfur-carbon composite material as described in any one of the first to twelfth embodiments, wherein the total content of the cross-linked product of the amphiphilic cardanol derivative may be 0.1-1 wt % based on the total weight of the sulfur-carbon composite material.
[0046] In another aspect of the present invention, a method for preparing a sulfur-carbon composite material according to any one of the following embodiments is provided.
[0047] According to a fourteenth embodiment of the present invention, there is provided a method for preparing a sulfur-carbon composite material, the method comprising the following steps:
[0048] preparing an uncoated sulfur-carbon composite material, the uncoated sulfur-carbon composite material comprising: a porous carbonaceous substrate; and a sulfur-containing compound supported in at least one of an outer surface of the porous carbonaceous substrate and an inner surface of a pore of the porous carbonaceous substrate;
[0049] coating the surface of the uncoated sulfur-carbon composite material entirely or at least partially with an amphiphilic cardanol derivative; and
[0050] Cross-linking at least a portion of the coated amphiphilic cardanol derivative to obtain a sulfur-carbon composite material whose surface is fully or partially coated with a cross-linked product of the amphiphilic cardanol derivative,
[0051] Wherein, the amphiphilic cardanol derivative is represented by the following chemical formula 1:
[0052] [Chemical formula 1]
[0053]
[0054] wherein R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl; and
[0055] R2 represents at least one selected from the group consisting of a C1-C10 alkyl group, a C2-C10 alkenyl group, and a C2-C10 alkynyl group, and has a structure substituted with at least one anionic functional group.
[0056] According to a fifteenth embodiment of the present invention, there is provided a method for preparing a sulfur-carbon composite material as defined in the fourteenth embodiment, the method may further include the step of preparing an amphiphilic cardanol derivative by alkylation of a cardanol derivative represented by the following Chemical Formula 6:
[0057] [Chemical formula 6]
[0058]
[0059] Wherein, R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl.
[0060] In still another aspect of the present invention, a positive electrode for a lithium-sulfur battery according to the following embodiment is provided.
[0061] According to a sixteenth embodiment of the present invention, there is provided a positive electrode for a lithium-sulfur battery, the positive electrode for a lithium-sulfur battery comprising: the sulfur-carbon composite material as defined in any one of the first to thirteenth embodiments; and a binder polymer.
[0062] In still another aspect of the present invention, a lithium-sulfur battery according to the following embodiment is provided.
[0063] According to a seventeenth embodiment of the present invention, there is provided a lithium-sulfur battery comprising a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode comprises the positive electrode as defined in the sixteenth embodiment.
[0064] Beneficial Effects
[0065] The sulfur-carbon composite material according to the present invention has a coating structure derived from a cross-linked product of an amphiphilic cardanol derivative, thereby being able to provide an effect of suppressing the dissolution of lithium polysulfide during operation of a lithium-sulfur battery including a positive electrode using the same. In this way, a lithium-sulfur battery having not only an improved discharge capacity but also an excellent battery capacity retention rate after repeated cycles can be provided.
[0066] In addition, due to the coating structure, the problem of positive electrode expansion during operation of the lithium-sulfur battery can be reduced, and a lithium-sulfur battery with improved safety can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0067] The accompanying drawings show preferred embodiments of the present invention and, together with the foregoing summary of the invention, are used to provide a further understanding of the technical features of the present invention, and thus the present invention is not interpreted as being limited to the accompanying drawings.
[0068] Figure 1 The method for preparing cardanol of Preparation Examples 1 and 2 is shown. 1 Spectrum of H NMR (nuclear magnetic resonance spectroscopy) results.
[0069] Figure 2 The amphiphilic cardanol derivative prepared according to Preparation Example 1 is shown. 1 Spectrum of H NMR results.
[0070] Figure 3 The cross-linked product of the amphiphilic cardanol derivative formed according to Example 1 is shown. 1 Partially extracted spectrum of H NMR results.
[0071] Figure 4Shown are graphs of thermogravimetric analysis (TGA) for preparing the porous carbonaceous substrate (KB) of Comparative Example 1, Comparative Example 1 (KB / S), Example 1 (c-CPS-KB / S 0.5 wt %), Example 2 (c-CPS-Li-KB / S 0.5 wt %), Example 3 (c-CPS-KB / S 1 wt %), Example 4 (c-CPS-KB / S 2 wt %), and Example 5 (c-CPS-KB / S 3 wt %).
[0072] Figure 5 Scanning electron microscope (SEM) images of Comparative Example 1 (KB / S), Example 1 (c-CPS-KB / S 0.5 wt %), Example 2 (c-CPS-Li-KB / S 0.5 wt %), Example 3 (c-CPS-KB / S 1 wt %), Example 4 (c-CPS-KB / S 2 wt %), and Example 5 (c-CPS-KB / S 3 wt %) are shown.
[0073] Figure 6 : is a graph showing the cycle test results of lithium-sulfur coin batteries using Comparative Example 1 and Examples 1, 3, 4 and 5.
[0074] Figure 7 : is a graph showing the cycle test results using the lithium-sulfur coin batteries of Comparative Example 1 and Examples 1 and 2. DETAILED DESCRIPTION
[0075] Hereinafter, the preferred embodiments of the present invention will be described in detail. However, the description proposed herein is only the preferred example for illustrative purposes only, is not intended to limit the scope of the present invention, and each constituent element can change in various ways or can be optionally combined. Therefore, it should be understood that other equivalents and variants can be made thereto without departing from the scope of the present invention.
[0076] Throughout the specification, the expression "a part includes or comprises an element" does not exclude the existence of any other elements but means that the part may further include other elements.
[0077] The specific terms used in the following description are for illustrative purposes and are not limiting. Directional terms such as "top", "bottom", "left", "right", "front", "back", "inside" or "outside" refer to directions in the drawings to which they refer, or to directions toward or away from the geometric center of the corresponding device, system and its components. In addition to the terms themselves, the terms also include: words containing them, their derivatives and words of similar meaning.
[0078] As used herein, each of the terms "alkyl," "alkenyl," and "alkyl" independently represents a linear or branched chain and refers to substituted or unsubstituted hydrocarbons.
[0079] The term "substituted or unsubstituted" means that the alkyl group is substituted with at least one substituent selected from the group consisting of deuterium, a halogen group, a nitrile group, a nitro group, a hydroxyl group, -COOH, an alkoxy group, an alkyl group, a cycloalkyl group, an alkenyl group, a cycloalkenyl group, an aryl group, a heterocyclic group containing at least one of N, O, S and P atoms, and a heteroaryl group.
[0080] In one aspect of the present invention, a sulfur-carbon composite material is provided, which can be used as a positive electrode material for a lithium-sulfur secondary battery.
[0081] The sulfur-carbon composite material comprises: a porous carbonaceous substrate; and a sulfur-containing compound contained in at least one of the outer surface of the porous carbonaceous substrate and the inner surface of the pores of the porous carbonaceous substrate, and the sulfur-carbon composite material is fully or partially surface-coated with a cross-linked product of an amphiphilic cardanol derivative represented by Chemical Formula 1.
[0082] As used herein, the term "amphiphilic" refers to the property of comprising both a non-polar hydrophobic portion and a polar hydrophilic portion. For example, an amphiphilic compound refers to a compound having a structure comprising both a non-polar hydrophobic portion and a polar hydrophilic portion. Thus, an "amphiphilic cardanol derivative" refers to a cardanol derivative having a structure comprising both a non-polar hydrophobic portion and a polar hydrophilic portion.
[0083] As used herein, the term "derivative" refers to a compound obtained by partial chemical changes of a compound and having a similar structure. Generally, such derivatives refer to compounds in which a hydrogen atom or a specific atomic group is replaced by another atom or atomic group. In a broad sense, products formed by addition reactions, etc. can be referred to as derivatives. Therefore, the term "cardanol derivative" not only refers to cardanol itself, but also generally includes compounds having a structure similar to cardanol through chemical changes of cardanol.
[0084] Herein, "cardanol" is one of the derivatives obtained from cashew nut shell liquid (CNSL), which is a natural vegetable oil extracted from the epidermis of cashew fruit belonging to the Anacardiaceae family (living in tropical forests), and can be represented by the following structural formula:
[0085] [Structural formula of cardanol]
[0086]
[0087] R=C 15 H 31-2n (where n=0, 1, 2 or 3).
[0088] As used herein, the term "amphiphilic cardanol derivative" generally refers to a compound having a structure similar to that of cardanol and modified in such a way that both a non-polar hydrophobic part and a polar hydrophilic part can be included in its structure. Herein, "modification" generally refers to a chemical reaction that partially or completely replaces the structure of a compound to induce a change in chemical properties.
[0089] In particular, according to the present invention, the amphiphilic cardanol derivative is represented by the following Chemical Formula 1:
[0090] [Chemical formula 1]
[0091]
[0092] wherein R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl; and
[0093] R2 represents at least one selected from the group consisting of a C1-C10 alkyl group, a C2-C10 alkenyl group, and a C2-C10 alkynyl group, and has a structure substituted with at least one anionic functional group.
[0094] The compound represented by Chemical Formula 1 is a phenol derivative substituted by R1 at the meta position and is one of the cardanol derivatives. The compound represented by Chemical Formula 1 contains a substituent (R1) having 10-50 carbon atoms, thereby containing a non-polar hydrophobic part. In addition, the compound represented by Chemical Formula 1 contains a substituent (R2) having 1-10 carbon atoms and at least one anionic functional group, thereby containing a hydrophilic part.
[0095] The compound represented by Chemical Formula 1 may form a cross-linked product through an addition reaction of an unsaturated bond between carbon atoms in its structure and / or through a condensation reaction of an alkoxy functional group.
[0096] According to one embodiment of the present invention, in the compound represented by Chemical Formula 1, at least one of R1 and R2 includes at least one unsaturated bond between carbon atoms, thereby forming a cross-linked product through the unsaturated bond between carbon atoms.
[0097] In this context, the term "unsaturated bonds between carbon atoms" refers to carbon (sp 2 ) = carbon (sp 2) double bonds and carbon (sp) ≡ carbon (sp) triple bonds. Therefore, the expression "at least one of R1 and R2 contains at least one unsaturated bond between carbon atoms" means that at least one of R1 and R2 represents a substituted or unsubstituted hydrocarbon in which all or part of the bonds between carbon atoms are double bonds and / or triple bonds. The unsaturated bonds between carbon atoms contained in the amphiphilic cardanol derivative can provide crosslinking sites in the crosslinked product of the amphiphilic cardanol derivative.
[0098] According to one embodiment of the present invention, as described below, the sulfur-carbon composite material can be fully or partially surface-coated with a cross-linked product of an amphiphilic cardanol derivative by fully or partially coating the surface of the sulfur-carbon composite material with the amphiphilic cardanol derivative and performing cross-linking.
[0099] According to one embodiment of the present invention, the non-polar portion in which R1 having a relatively longer carbon chain is located in the structure of the amphiphilic cardanol derivative can provide excellent binding force with the porous carbonaceous substrate, and the polar portion having a relatively shorter carbon chain and containing anionic functional groups located therein can impart surface hydrophilicity to the sulfur-carbon composite material.
[0100] According to one embodiment of the present invention, the surface of the sulfur-carbon composite material entirely or partially surface-coated with the cross-linked product of the amphiphilic cardanol derivative may show a negative zeta (ζ) potential.
[0101] In particular, the surface of the sulfur-carbon composite material may exhibit a zeta potential satisfying the following formula 1:
[0102] [Formula 1]
[0103] -60 mV≤ζ≤0 mV
[0104] According to the present invention, the zeta potential may show a measurement error depending on an instrument used for measurement, but, for example, may show a value measured by using a zeta potential tester (ELSZ-1000, OTSUKA Electronics) after preparing a dispersion containing a sulfur-carbon composition at a concentration of 0.01 wt % in water as a solvent.
[0105] According to one embodiment of the present invention, the amphiphilic cardanol derivative is modified so that at least one anionic functional group may exist in the structure of R2, wherein the anionic functional group may be substituted at one end of R2. For example, R2 may be -(CH x ) n Q represents (wherein, x=0, 1 or 2, n is an integer of 1 to 10, and Q is an anionic functional group).
[0106] In this article, anionic functional groups refer to functional groups that can provide anions in aqueous solvents. For example, compounds containing anionic functional groups can have dissociated cations such as protons (H + ) properties, so that it can provide anions (-) in aqueous solvents such as water.
[0107] According to one embodiment of the present invention, the anionic functional group may be provided in an aqueous solvent. - 、-SO3 - 、-COO - or -SO4 2- In particular, the anionic functional group may include at least one selected from the following: - 、-SO3 - 、-COO - 、-SO4 2- and its conjugate acid.
[0108] According to one embodiment of the present invention, the amphiphilic cardanol derivative may further include alkali metal ions and / or alkaline earth metal ions as conjugated ions of anions in the anionic functional groups contained in its structure. In particular, the anionic functional groups contained in R2 may further include at least one of alkali metal ions and alkaline earth metal ions as conjugated ions. When R2 further includes conjugated ions of anionic functional groups, it may provide a favorable effect in terms of the conductivity of the positive electrode using the sulfur-carbon composite material, but the scope of the present invention is not limited thereto.
[0109] Specific examples of alkali metal ions may include lithium ions (Li + ), sodium ion (Na + ) or potassium ion (K + ), but not limited thereto. Specific examples of alkaline earth metal ions may include calcium ions (Ca 2+ ), magnesium ion (Mg 2+ ) or beryllium ion (Be 2+ ), but are not limited to them.
[0110] According to one embodiment of the present invention, the anionic functional group may be at least one selected from the following: -SO3 - 、-COO - 、-SO4 2- , -SO3H, -COOH, -SO4H, -SO3 - M + 、-COO - M + 、-SO4 2- M2 + and -SO4 2- M 2+(wherein M is an alkali metal ion or an alkaline earth metal ion).
[0111] According to another embodiment of the present invention, at least one anionic functional group contained in the structure of R2 may include at least one of the following: -SO3 - , -SO3H and -SO3 - M + (wherein M is an alkali metal ion).
[0112] According to one embodiment of the present invention, the anionic functional group contained in the amphiphilic cardanol derivative can provide anions to the surface of the sulfur-carbon composite material coated with the cross-linked product of the amphiphilic cardanol derivative. Therefore, the effect of improving the conductivity of the sulfur-carbon composite material can be provided, but the effect of the present invention is not limited thereto.
[0113] As described above, the unsaturated bonds between carbon atoms contained in the amphiphilic cardanol derivative provide crosslinking sites in the crosslinked product of the amphiphilic cardanol derivative. In particular, the amphiphilic cardanol derivative contains at least one unsaturated bond between carbon atoms. Therefore, the crosslinked product of the amphiphilic cardanol derivative is formed by crosslinking between two or more amphiphilic cardanol derivative molecules and / or in one amphiphilic cardanol derivative molecule.
[0114] According to one embodiment of the present invention, the cross-linking between the unsaturated bonds of the amphiphilic cardanol derivatives can be determined by comparing the structural changes of the amphiphilic cardanol derivatives before and after cross-linking. 1 In the H-NMR graph, crosslinking can be determined by a decrease in the peak intensity of unsaturated bonds (e.g., C=C, C≡C, etc.) and an increase in the peak intensity of saturated bonds (e.g., CC). In addition, the formation of a crosslinked product of the amphiphilic cardanol derivative can be determined by a known analytical method capable of determining a change in the number of unsaturated bonds between carbon atoms.
[0115] According to one embodiment of the present invention, the degree of crosslinking of the crosslinked product of the amphiphilic cardanol derivative as determined by the following formula 2 may be 15%-45%, particularly 20%-40%, more particularly 25%-35%:
[0116] [Formula 2]
[0117] Cross-linking degree (%) = (carbon unsaturation degree of the cross-linked product of the amphiphilic cardanol derivative / carbon unsaturation degree of the amphiphilic cardanol derivative) × 100
[0118] In Formula 2, the carbon unsaturation degree of each of the amphiphilic cardanol derivative and the cross-linked product of the amphiphilic cardanol derivative can be determined by a known method for determining carbon unsaturation, and then the cross-linking degree can be calculated according to Formula 2.
[0119] An example of a method for determining carbon unsaturation may include 1 H NMR analysis. For example, the carbon unsaturation degree can be determined by dividing the peak area of the unsaturated bond between carbon atoms of the cross-linked product of the amphiphilic cardanol derivative by the peak area of the unsaturated bond between carbon atoms of the amphiphilic cardanol derivative before cross-linking.
[0120] According to one embodiment of the present invention, 1 H NMR analysis can be performed by known methods. For example, 1 H NMR can be performed by using a sample dissolved in DMSO-d6 as a solvent and a 400 MHz NMR instrument.
[0121] According to one embodiment of the present invention, the number of carbon atoms of R1 in Chemical Formula 1 is important because R1 imparts hydrophobicity to the cross-linked product of the amphiphilic cardanol derivative and improves adhesion to the porous carbonaceous substrate.
[0122] R1 is at least one selected from the group consisting of a C10-C50 alkyl group, a C10-C50 alkenyl group, and a C10-C50 alkynyl group.
[0123] According to one embodiment of the present invention, R1 may be particularly selected from at least one of C10-C40 alkyl, C10-C40 alkenyl and C10-C40 alkynyl, more particularly, may be selected from at least one of C10-C30 alkyl, C10-C30 alkenyl and C10-C30 alkynyl. More particularly, R1 may be particularly selected from at least one of C13-C20 alkyl, C13-C20 alkenyl and C13-C20 alkynyl. According to one embodiment of the present invention, the amphiphilic cardanol derivative may have a structure in which R1 has 10-30 carbon atoms and the number of unsaturated bonds between carbon atoms is 0 (i.e., saturated hydrocarbon group) to 5, particularly 0 to 4 or 0 to 3.
[0124] According to another embodiment of the present invention, the amphiphilic cardanol derivative may include a compound having at least one structure selected from the following Chemical Formula 2 to Chemical Formula 5:
[0125] [Chemical formula 2]
[0126]
[0127] [Chemical formula 3]
[0128]
[0129] [Chemical formula 4]
[0130]
[0131] [Chemical formula 5]
[0132]
[0133] According to another embodiment of the present invention, the amphiphilic cardanol derivative may be a mixture of two or more derivatives having different R1. In particular, the amphiphilic cardanol derivative may be a mixture of derivatives in which R1 has a structure represented by Chemical Formula 2 to Chemical Formula 5.
[0134] According to another embodiment of the present invention, the amphiphilic cardanol derivative may include 1-10 parts by weight of the structure in which R1 represents Chemical Formula 2, 40-70 parts by weight of the structure in which R1 represents Chemical Formula 3, 5-25 parts by weight of the structure in which R1 represents Chemical Formula 4, and 25-40 parts by weight of the structure in which R1 represents Chemical Formula 5.
[0135] Particularly, the amphiphilic cardanol derivative may include 3-7 parts by weight of the structure wherein R1 represents Chemical Formula 2, 45-60 parts by weight of the structure wherein R1 represents Chemical Formula 3, 10-20 parts by weight of the structure wherein R1 represents Chemical Formula 4, and 25-30 parts by weight of the structure wherein R1 represents Chemical Formula 5.
[0136] According to one embodiment of the present invention, the number of carbon atoms of R2 in Chemical Formula 1 is important because R2 imparts hydrophilicity to the cross-linked product of the amphiphilic cardanol derivative and improves the conductivity of the sulfur-carbon composite material.
[0137] R2 represents at least one selected from the group consisting of a C1-C10 alkyl group, a C2-C10 alkenyl group, and a C2-C10 alkynyl group, and has a structure substituted with at least one anionic functional group at an optional position.
[0138] According to one embodiment of the present invention, R2 may specifically be at least one selected from C2-C8 alkyl, C2-C8 alkenyl and C2-C8 alkynyl, and more specifically at least one selected from C3-C5 alkyl, C3-C5 alkenyl and C3-C5 alkynyl.
[0139] According to one embodiment of the present invention, the amphiphilic cardanol derivative may have a structure in which R2 has 2 to 5 carbon atoms and has a terminal thereof substituted with an anionic functional group.
[0140] According to one embodiment of the present invention, R2 may be a 3-propylsulfonic acid group.
[0141] According to one embodiment of the present invention, the amphiphilic cardanol derivative may include cardanolylpropyl sulfonic acid represented by the following Chemical Formula 7:
[0142] [Chemical formula 7]
[0143]
[0144] Where R is C 15 H 31-2n (where n=0, 1, 2 or 3).
[0145] According to one embodiment of the present invention, the structure of the sulfur-carbon composite material can be divided into a coating structure formed of a cross-linked product of an amphiphilic cardanol derivative and a core structure containing a porous carbonaceous substrate and a sulfur-containing compound.
[0146] The porous carbonaceous substrate forming the core structure can be used to improve the conductivity of the sulfur-carbon composite material and load the sulfur-containing compound, thereby improving the utilization efficiency of sulfur, but the mechanism of the present invention is not limited thereto.
[0147] The porous carbonaceous substrate is a material having a large number of fine pores, and the sulfur-containing compound is supported in at least one of the outer surface of the porous carbonaceous substrate and the inner surface of the pores of the porous carbonaceous substrate.
[0148] According to one embodiment of the present invention, the porous carbonaceous substrate comprises a large number of pores on its surface and inside thereof. For example, the average diameter of the pores may be 5-100 nm, particularly 5-80 nm, 5-60 nm or 5-50 nm.
[0149] The porous carbonaceous substrate is not particularly limited in terms of its material as long as it contains a large number of fine pores as described above and can support the sulfur-containing compound.
[0150] According to one embodiment of the present invention, specific examples of the material of the porous carbonaceous substrate include: carbon black, carbon fiber, carbon nanotube (CNT), graphene, graphene oxide (GO), reduced graphene oxide (rGO), graphite, graphite nanofiber (GNF), carbon nanofiber (CNF), activated carbon fiber (ACF), natural graphite, artificial graphite, expanded graphite, activated carbon, fullerene or two or more thereof.
[0151] According to one embodiment of the present invention, when carbon nanotubes are used as the material of the porous carbonaceous substrate, the carbon nanotubes may include single-walled carbon nanotubes (SWCNTs), multi-walled carbon nanotubes (MWCNTs), or both.
[0152] According to another embodiment of the present invention, when carbon nanotubes are used as a material of the porous carbonaceous substrate, the carbon nanotubes may include entangled carbon nanotubes (entangled CNTs) formed as a secondary structure by aggregation of a plurality of carbon nanotubes as a primary structure.
[0153] According to one embodiment of the present invention, due to the interstitial volume formed by the entanglement of the carbon nanotubes as the primary structure, the entangled carbon nanotubes may be characterized in that they have improved porosity compared to the carbon nanotubes as the primary structure.
[0154] According to one embodiment of the present invention, the size of the porous carbonaceous substrate may be 10-100 μm, particularly 20-50 μm, but is not limited thereto. When the size of the porous carbonaceous substrate falls within the above-defined range, advantageous effects may be provided in the following aspects: controlling the solid content during the preparation of the slurry for forming the electrode active material layer, and the physical properties of the electrode such as adhesion, and the performance (output, capacity, etc.) of the battery.
[0155] According to one embodiment of the present invention, the pore volume of the porous carbonaceous substrate may be 1-5 cm 3 / g, especially 1-4 cm 3 For example, the pore volume may be a value determined by calculation based on N2 isotherm analysis of liquid nitrogen adsorption.
[0156] According to one embodiment of the present invention, the BET specific surface area of the porous carbonaceous substrate may be 150-2,000 m 2 / g, especially 250-700 m 2 / g, but not limited thereto. The BET specific surface area is measured by the BET method and may be a value measured by a known method. For example, the BET specific surface area may be measured by nitrogen adsorption at liquid nitrogen temperature (77 K) using BELSORP mini II available from BEL Japan Co.
[0157] According to one embodiment of the present invention, the sulfur-containing compound may include inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 2≤x≤8), a disulfide compound or a mixture of two or more thereof, but not limited thereto.
[0158] According to one embodiment of the present invention, the porous carbonaceous substrate and the sulfur-containing compound may be mixed in a weight ratio of 1:9-9:1, specifically 2:8-8:2, more specifically 3:7-7:3 or 4:6-2:8.
[0159] According to one embodiment of the present invention, the core structure of the sulfur-carbon composite material can be formed by mixing the porous carbonaceous substrate with the sulfur-containing compound and then heat treating. For example, the heat treatment can be performed at a temperature of 130-200°C, particularly 130-180°C or 150-160°C.
[0160] As described above, in one aspect of the present invention, a sulfur-carbon composite material is provided, which comprises: a porous carbonaceous substrate; and a sulfur-containing compound contained in at least one of the outer surface of the porous carbonaceous substrate and the inner surface of the pores of the porous carbonaceous substrate, and the sulfur-carbon composite material is fully or partially surface-coated with a cross-linked product of an amphiphilic cardanol derivative represented by Chemical Formula 1.
[0161] According to one embodiment of the present invention, the average particle size (D 50 ) can be 10-100 μm, in particular 20-50 μm.
[0162] According to one embodiment of the present invention, the total content of the cross-linked product of the amphiphilic cardanol derivative may be 0.1-10 wt % based on the total weight of the sulfur-carbon composite material, but is not limited thereto. In particular, the total content of the cross-linked product of the amphiphilic cardanol derivative may be 0.1-5 wt %, particularly 0.1-1 wt %, 0.3-1 wt % or 0.3-0.8 wt % based on the total weight of the sulfur-carbon composite material. When the content of the cross-linked product of the amphiphilic cardanol derivative falls within the above-defined range, a more favorable effect can be provided in terms of improving the life of a lithium-sulfur battery using the sulfur-carbon composite material, but the scope of the present invention is not limited thereto.
[0163] In another aspect of the present invention, a method for preparing the above sulfur-carbon composite material is provided.
[0164] The method for preparing the sulfur-carbon composite material comprises the following steps:
[0165] preparing an uncoated sulfur-carbon composite material, the uncoated sulfur-carbon composite material comprising: a porous carbonaceous substrate; and a sulfur-containing compound supported in at least one of an outer surface of the porous carbonaceous substrate and an inner surface of a pore of the porous carbonaceous substrate;
[0166] coating the surface of the uncoated sulfur-carbon composite material entirely or at least partially with an amphiphilic cardanol derivative; and
[0167] At least a portion of the coated amphiphilic cardanol derivative is cross-linked to obtain a sulfur-carbon composite material whose surface is fully or partially coated with a cross-linked product of the amphiphilic cardanol derivative.
[0168] In this method, reference will be made to the above description regarding the porous carbonaceous substrate, the sulfur-containing compound, the amphiphilic cardanol derivative, and the cross-linked product of the amphiphilic cardanol derivative.
[0169] According to one embodiment of the present invention, the method for preparing the sulfur-carbon composite material may further include the step of preparing an amphiphilic cardanol derivative by alkylation of a cardanol derivative represented by the following Chemical Formula 6:
[0170] [Chemical formula 6]
[0171]
[0172] Wherein, R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl.
[0173] First, the step of preparing the uncoated sulfur-carbon composite material includes mixing the porous carbonaceous substrate with the sulfur-containing compound. According to one embodiment of the present invention, the porous carbonaceous substrate and the sulfur-containing compound can be mixed in a weight ratio of 1:9-9:1, particularly 2:8-8:2, more particularly 3:7-7:3 or 4:6-2:8.
[0174] According to one embodiment of the present invention, the method may further include a step of pulverizing the porous carbonaceous substrate and the sulfur-containing compound after mixing the porous carbonaceous substrate and the sulfur-containing compound. The mixing uniformity of the porous carbonaceous substrate and the sulfur-containing compound can be improved by pulverizing, but the scope of the present invention is not limited thereto.
[0175] According to one embodiment of the present invention, the step of preparing the uncoated sulfur-carbon composite material includes a step of performing a heat treatment after mixing (or mixing and pulverizing) the porous carbonaceous substrate with the sulfur-containing compound. For example, the heat treatment can be performed at a temperature of 130-200° C., particularly 130-180° C. or 150-160° C. The mechanical strength of the obtained sulfur-carbon composite material can be improved by heat treatment, but the scope of the present invention is not limited thereto.
[0176] Next, the surface of the uncoated sulfur-carbon composite material is completely or at least partially coated with an amphiphilic cardanol derivative.
[0177] According to one embodiment of the present invention, the sulfur-carbon composite material can be coated by contacting the sulfur-carbon composite material with the amphiphilic cardanol derivative. For example, the surface of the sulfur-carbon composite material can be coated by immersing the sulfur-carbon composite material in a dispersion containing the amphiphilic cardanol derivative dispersed therein and stirring.
[0178] According to one embodiment of the present invention, the dispersion liquid containing the amphiphilic cardanol derivative dispersed therein may include the amphiphilic cardanol derivative dispersed in an aqueous solvent such as water at a concentration of 0.1-10 wt %, but the scope of the present invention is not limited thereto.
[0179] According to one embodiment of the present invention, based on the total weight of the sulfur-carbon composite material, the content of the coated amphiphilic cardanol derivative may be 0.1-10 wt %, 0.1-5 wt %, 0.1-3 wt %, 0.1-1 wt % or 0.3-0.8 wt %. The content of the coated amphiphilic cardanol derivative can be calculated by the weight increase of the coated sulfur-carbon composite material compared to the uncoated sulfur-carbon composite material.
[0180] Then, the unsaturated bonds between carbon atoms in the coated amphiphilic cardanol derivative are cross-linked to form a cross-linked product. The surface of the sulfur-carbon composite material can be fully or partially coated with the cross-linked product of the amphiphilic cardanol derivative by cross-linking.
[0181] According to one embodiment of the present invention, crosslinking can be carried out in the presence of a polymerization initiator. For example, the polymerization initiator can be an azo initiator and can be obtained from V-501 (CAS RN ® 2638-94-0,C 12 H 16 N4O4, MW 280.28 g / mol, Fuji Film Wako Pure Chemical Corp.) is commercially available, but not limited thereto.
[0182] According to one embodiment of the present invention, crosslinking may be preferably performed at a temperature at which the amphiphilic cardanol derivative does not decompose. For example, crosslinking may be performed at 60-100°C, 70-95°C, 80-95°C or 90-95°C, but is not limited thereto.
[0183] According to one embodiment of the present invention, the method for preparing the sulfur-carbon composite material may further include a step of preparing an amphiphilic cardanol derivative to be used in the step of coating the uncoated sulfur-carbon composite material.
[0184] According to one embodiment of the present invention, the amphiphilic cardanol derivative may be prepared by alkylation of a cardanol derivative represented by the following Chemical Formula 6:
[0185] [Chemical formula 6]
[0186]
[0187] Wherein, R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl.
[0188] According to one embodiment of the present invention, with respect to R1 in Chemical Formula 6, reference will be made to the description of R1 in Chemical Formula 1 above.
[0189] According to one embodiment of the present invention, the alkylation of the cardanol derivative represented by Chemical Formula 6 is a reaction in which R2 replaces the hydrogen atom of the hydroxyl group (OH) in Chemical Formula 6. Herein, R2 in Chemical Formula 6 will refer to the description of R2 in Chemical Formula 1 above.
[0190] According to one embodiment of the present invention, the alkylation of the cardanol derivative represented by Chemical Formula 6 can be performed by replacing the hydrogen atoms of the hydroxyl group of the cardanol derivative represented by Chemical Formula 6 with at least one selected from a C1-C10 alkyl group, a C2-C10 alkenyl group, and a C2-C10 alkynyl group, and then replacing at least one hydrogen atom of the resulting substituted structure with an anionic functional group to achieve amphiphilic modification.
[0191] According to one embodiment of the present invention, the amphiphilic modification step can be performed by alkylating the cardanol derivative, replacing the resulting alkyl substituted structure with at least one functional group selected from sulfonic acid group, carboxylic acid group and sulfate group, and then replacing the proton (H) of the acid compound with an alkali metal ion and / or an alkaline earth metal ion. + ) to carry out.
[0192] According to one embodiment of the present invention, the alkylation may be performed by a ring-opening reaction of an alkyl sultone. Herein, the cardanol derivative alkylated by a ring-opening reaction of an alkyl sultone may include a sulfonic acid group as an anionic functional group.
[0193] In this way, a sulfur-carbon composite material can be obtained, which comprises: a porous carbonaceous substrate; and a sulfur-containing compound contained in at least one of the outer surface of the porous carbonaceous substrate and the inner surface of the pores of the porous carbonaceous substrate, and the sulfur-carbon composite material is fully or partially surface-coated with a cross-linked product of the amphiphilic cardanol derivative represented by Chemical Formula 1.
[0194] In another aspect of the present invention, a positive electrode for a lithium-sulfur battery is provided, wherein the positive electrode for a lithium-sulfur battery comprises the sulfur-carbon composite material and a binder polymer.
[0195] According to one embodiment of the present invention, the binder polymer can be used without particular limitation as long as it is a binder that can be used for the positive electrode of a lithium-sulfur battery. For example, the binder may include polyvinylidene fluoride (PVDF), particularly PVDF dispersed in N-methyl-2-pyrrolidone (NMP), but is not limited thereto.
[0196] According to another embodiment of the present invention, the binder polymer may include an aqueous binder such as styrene-butadiene rubber (SBR), particularly an aqueous binder dispersed in an aqueous solvent such as water, but not limited thereto.
[0197] According to another embodiment of the present invention, the positive electrode for a lithium-sulfur battery may further include a conductive material, an additive, etc. in addition to the binder. Herein, any conventional types of conductive materials and additives may be used, and thus a detailed description thereof will be omitted.
[0198] According to yet another embodiment of the present invention, a positive electrode for a lithium-sulfur battery may include a positive electrode collector, and a positive electrode active material layer coated on one surface or both surfaces of the positive electrode collector and including a combination of a sulfur-carbon composite material and a binder polymer.
[0199] Herein, the positive electrode current collector is not particularly limited as long as it has high conductivity while not causing any chemical changes in the corresponding battery.
[0200] According to one embodiment of the present invention, the positive electrode including the sulfur-carbon composite material shows excellent effects in initial capacity and cycle stability, but the effects of the present invention are not limited thereto.
[0201] In another aspect of the present invention, a lithium-sulfur battery is provided, comprising a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte, wherein the positive electrode comprises the above-mentioned positive electrode.
[0202] According to one embodiment of the present invention, there are no particular limitations on the negative electrode and the separator as long as they can be used in a lithium-sulfur battery without impairing the purpose of the present invention. For example, the negative electrode may include lithium metal.
[0203] According to one embodiment of the present invention, there is no particular limitation on the separator as long as it can be used as a separator for a lithium-sulfur battery. For example, the separator may include a porous polyolefin substrate, and if necessary, may further include inorganic particles on at least one surface of the porous polyolefin substrate. In addition, if necessary, the separator may further include a binder for bonding the inorganic particles.
[0204] According to another embodiment of the present invention, the separator may be a film-like electrolyte membrane containing a solid electrolyte, and if necessary, may further contain a binder for bonding the solid electrolyte. There is no particular limitation on the solid electrolyte as long as it can be generally used in lithium-sulfur batteries. Specific examples of the solid electrolyte may include a polymer solid electrolyte, an inorganic solid electrolyte, or a combination thereof.
[0205] According to one embodiment of the present invention, the electrolyte includes an electrolyte commonly used in lithium-sulfur batteries. The electrolyte may contain a lithium salt and a non-aqueous solvent.
[0206] According to one embodiment of the present invention, there is no particular limitation on the lithium salt as long as it can be generally used in the electrolyte of a lithium-sulfur battery. Specific examples of the lithium salt may include, but are not limited to: LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborane, lithium lower aliphatic carboxylate, lithium tetraphenylborate, lithium imide or two or more thereof.
[0207] There is no particular limitation on the nonaqueous solvent as long as it can be generally used in the electrolyte of lithium-sulfur batteries. Specific examples of the nonaqueous solvent may include, but are not limited to, cyclic carbonate solvents, linear carbonate solvents, ester solvents, ketone solvents, or mixed solvents containing two or more thereof.
[0208] According to one embodiment of the present invention, the electrolyte may include (CF3SO2)2NLi as a lithium salt and a binary solvent of dioxolane (DOL) / dimethoxyethane (DME) as a non-aqueous solvent. For example, the electrolyte may further include conventional additives such as LiNO3.
[0209] According to one embodiment of the present invention, the outer shape of the lithium-sulfur battery can be selected from a coin-like shape, a cylindrical shape, a pouch-like shape, or a prismatic shape without particular limitation. In addition, the lithium-sulfur battery can be used not only as a battery cell used as a power source for a compact device, but also as a unit cell in a medium-to-large battery module including a plurality of battery cells, and its application is not particularly limited.
[0210] According to one embodiment of the present invention, a lithium-sulfur battery using a positive electrode comprising a sulfur-carbon composite material suppresses the dissolution of lithium polysulfide during operation of the battery to reduce the shuttle effect, thereby being able to effectively improve the problem of capacity reduction caused by repeated cycles, but the effects of the present invention are not limited thereto.
[0211] According to one embodiment of the present invention, the lithium-sulfur battery can provide an effect of improving energy density by increasing the sulfur loading amount in the positive electrode, but the effect of the present invention is not limited thereto.
[0212] Hereinafter, the method for preparing the sulfur-carbon composite material according to the embodiment of the present invention and the method for manufacturing the lithium-sulfur battery using the same will be described in more detail with reference to examples. However, the following examples are only for illustrative purposes only, and the scope of the present invention is not limited thereto.
[0213] [Preparation of amphiphilic cardanol derivatives]
[0214] An amphiphilic cardanol derivative was prepared by using cardanol having a structure as described below. Figure 1 The cardanol used in this article is shown 1 H NMR analysis results. In the following structures, a to d represent Figure 1 As shown in 1 The H NMR peaks correspond to the signs.
[0215]
[0216] Preparation Example 1. Preparation of Cardanoyl Propyl Sulfonic Acid (CPS)
[0217] According to the reaction scheme described below, cardanolylpropylsulfonic acid as an amphiphilic cardanol derivative was prepared as follows.
[0218]
[0219] First, 3 g of cardanol and 2.24 g of potassium tert-butoxide (Sigma-Aldrich) were stirred in ethanol (Daejung Co.) as a solvent at room temperature (23° C.) to activate a hydroxyl group (—OH).
[0220] Propane sultone (TCI Co.) dissolved in ethanol was added to the activated cardanol monomer, and a reaction was performed at 80° C. for 40 hours to obtain cardanolyl propane sultone.
[0221] Cardanoylpropyl sultone was dissolved in water, an equal amount or more of HCl (Daejung Co.) was introduced thereto, and the resulting mixture was stirred at room temperature for protonation, thereby providing cardanoylpropyl sulfonic acid (CPS) (yield 50%).
[0222] Then, proceed 1 H NMR was used to confirm whether cardanoylpropyl sulfonic acid was obtained. Figure 2 Shows 1 Results of H NMR analysis.
[0223] Preparation Example 2. Preparation of Lithium Cardanoyl Propyl Sulfonate (CPS-Li)
[0224] The product of Preparation Example 1 (cardanoylpropyl sulfonic acid, CPS) and LiOH were dissolved in water in equal amounts and stirred to obtain lithium cardanoylpropyl sulfonate (CPS-Li).
[0225] [Preparation of sulfur-carbon composite materials]
[0226] The sulfur-carbon composite materials according to each of Comparative Example 1 and Examples 1 to 5 were obtained as follows.
[0227] Comparative Example 1. KB-S
[0228] Sulfur (S8) and Ketjen black (KB) (Lion Corp.) were mixed in a weight ratio of 7:3, and the resulting mixture was pulverized by using a mortar grinder and heat-treated at 155°C for 30 minutes to obtain an uncoated sulfur-carbon composite material (KB-S), wherein the uncoated sulfur-carbon composite material (KB-S) includes sulfur supported on the outer surface of Ketjen black and the inner surfaces of the pores of Ketjen black.
[0229] Example 1. c-CPS-KB / S 0.5 wt%
[0230] First, 100 parts by weight of the uncoated sulfur-carbon composite material prepared according to Comparative Example 1 and 0.5 parts by weight of Preparation Example 1 (cardanoylpropyl sulfonic acid, CPS) as an amphiphilic cardanol derivative were introduced into 300 mL of water and ultrasonically treated for 5 hours. The resulting mixture was stirred for 16 hours and washed with water to coat the surface of the uncoated sulfur-carbon composite material with the amphiphilic cardanol derivative according to Preparation Example 1.
[0231] Next, 10 wt % of a polymerization initiator (V-501, Fuji Film Wako Pure Chemical Corp.) based on the total weight of the sulfur-carbon composite material coated with the amphiphilic cardanol derivative was stirred with 2 mL of water at 90° C. for 24 hours, followed by washing to obtain a sulfur-carbon composite material coated with a cross-linked product of the amphiphilic cardanol derivative.
[0232] Figure 3 The obtained sulfur-carbon composite material 1 H NMR analysis results of the peak area of the cross-linked product of the amphiphilic cardanol derivative. Figure 3 , from amphiphilic cardanol derivatives 1 H NMR analysis results ( Figure 2 ) 1 The decrease in the H peak shows that the cross-linked product is formed through unsaturated bonds between carbon atoms.
[0233] In particular, refer to Figure 2 and Figure 3It can be seen that the degree of crosslinking is 30% of the ratio of the unsaturated bond content of the crosslinked product of the amphiphilic cardanol derivative after crosslinking to the unsaturated bond content of the amphiphilic cardanol derivative before crosslinking.
[0234] Crosslinking degree (%) = [the content of unsaturated bonds in the crosslinked product of the amphiphilic cardanol derivative ( Figure 3 ) / Unsaturated bond content of amphiphilic cardanol derivatives ( Figure 2 )]×100
[0235] Example 2. c-CPS-Li-KB / S 0.5 wt%
[0236] A sulfur-carbon composite material was obtained in the same manner as in Example 1, except that Preparation Example 2 was used as the amphiphilic cardanol derivative.
[0237] Example 3. c-CPS-KB / S 1 wt%
[0238] A sulfur-carbon composite material was obtained in the same manner as in Example 1, except that Preparation Example 1 was used as the amphiphilic cardanol derivative in an amount of 1 part by weight.
[0239] Example 4. c-CPS-KB / S 2 wt%
[0240] A sulfur-carbon composite material was obtained in the same manner as in Example 1, except that Preparation Example 1 was used as the amphiphilic cardanol derivative in an amount of 2 parts by weight.
[0241] Example 5. c-CPS-KB / S 3 wt%
[0242] A sulfur-carbon composite material was obtained in the same manner as in Example 1, except that Preparation Example 1 was used as the amphiphilic cardanol derivative in an amount of 3 parts by weight.
[0243] Composition analysis of sulfur-carbon composite materials
[0244] The compositions of the sulfur-carbon composite materials prepared as described above are shown in Table 1 below.
[0245] The sulfur content in the obtained sulfur-carbon composite material was determined by using a thermogravimetric analysis (TGA) instrument (TA instruments TGA55) at 100°C isothermal conditions for 10 minutes and then heating the temperature from 100°C to 700°C at a rate of 10°C / min. The results are shown in Figure 4 middle.
[0246]
[0247] Refer to Table 1 and Figure 4, sulfur (S8) is insoluble in water at room temperature but has sublimation characteristics, and thus it is believed that sulfur is partially lost at the temperature at which cross-linking is performed. In particular, in the case of Examples 1 and 2, the coating layer of the cross-linked product of the amphiphilic cardanol derivative is formed to a relatively uniform thickness to minimize the loss of sulfur. However, in the case of Examples 3 and 4, it is believed that the loss of sulfur is partially increased, and the thickness of the coating layer becomes slightly uneven. In addition, in the case of Example 5, the cross-linked product of the excessive amphiphilic cardanol derivative covers most of the surface of KB / S, and thus it is believed that Example 5 shows a reduction in sulfur loss compared to Examples 3 and 4.
[0248] Structural Analysis of Sulfur-Carbon Composite Materials
[0249] Figure 5 Scanning electron microscope (SEM) images of the sulfur-carbon composite materials according to Comparative Example 1 and Examples 1-5, respectively, are shown.
[0250] from Figure 5 It can be seen that each sulfur-carbon composite material prepared as described above comprises an average particle size (D 50 ) are spherical particles of 35 μm.
[0251] In addition, refer to Figure 5 In the case of Examples 1 and 2, it can be seen that the surface of each sulfur-carbon composite material is uniformly coated with the cross-linked product of the amphiphilic cardanol derivative without aggregation. In contrast, in the case of Examples 3-5 using an increased amount of the amphiphilic cardanol derivative, it can be seen that the cross-linked product causes aggregation, resulting in a decrease in the uniformity of the coating structure on the surface of the sulfur-carbon composite material.
[0252] [Evaluation of the performance of lithium-sulfur coin batteries]
[0253] In order to evaluate the battery performance when the sulfur-carbon composite material prepared as described above was used for the positive electrode, a lithium-sulfur coin cell was obtained as follows.
[0254] The sulfur-carbon composite material prepared as described above, polyacrylic acid (PAA) (Mw 450,000) as a binder, and carbon (Super P) as a conductive material were mixed in a ratio of 85:10:5, 0.5 wt % of PVA (Mw 9,500) as a dispersant was added thereto, and mixed by using a mixer (Thinky Co.) until the solid content in the aqueous phase was 13 wt %, thereby providing a positive electrode slurry. The obtained positive electrode slurry was coated on an aluminum foil by using a doctor blade to a thickness of 300 μm and dried at 50° C. for 14 hours.
[0255] A positive electrode and lithium metal as a negative electrode were prepared, a Celgard separator was inserted between the positive electrode and the negative electrode to provide an electrode assembly, and the electrode assembly was immersed in a liquid electrolyte containing 1 M LiTFSI and 0.2 M LiNO3 in DOL / DME (1 / 1, volume / volume). In this way, a lithium-sulfur coin cell was obtained.
[0256] Evaluation of discharge capacity after repeated cycles
[0257] The battery cycle tester (WBS3000 battery cycler, WonATech) was used to test the battery at 25 °C at a current density of 0.5 C and a current density of 1.8-2.8 V (vs. Li / Li + ) to perform a charge / discharge cycle test.
[0258] The evaluation results of the discharge capacity after repeated cycles are shown in Figure 6 and Figure 7 middle.
[0259] exist Figure 6 and Figure 7 %, c-CPS-KB / S 0.5 wt % represents Example 1, c-CPS-Li-KB / S 0.5 wt % represents Example 2, c-CPS-KB / S 1 wt % represents Example 3, c-CPS-KB / S 2 wt % represents Example 4, and c-CPS-KB / S 3 wt % represents Example 5.
[0260] Reference Figure 6 , the lithium-sulfur batteries using the sulfur-carbon composite materials according to Examples 1 and 3-5, respectively, show improved initial capacity retention rates compared to Comparative Example 1. It can be seen that as the number of cycles increases, Example 1 shows the highest long-term life characteristics.
[0261] Reference Figure 7 Similarly, the lithium-sulfur batteries using the sulfur-carbon composite materials according to Examples 1 and 2, respectively, showed improved capacity retention compared to Comparative Example 1. On the other hand, it can be seen that although the sulfur-carbon composite material of Example 2 contains the cross-linked product of the amphiphilic cardanol derivative containing Li ions of Preparation Example 2 as a coating layer, thereby improving the conductivity of the surface of the sulfur-carbon composite material, the amphiphilic cardanol derivative according to Preparation Example 1 is more useful in terms of battery capacity.
Claims
1. A sulfur-carbon composite material, comprising: a porous carbonaceous substrate; and a sulfur-containing compound contained in at least one of an outer surface of the porous carbonaceous substrate and an inner surface of a pore of the porous carbonaceous substrate, and The sulfur-carbon composite material is entirely or partially coated on the surface with a cross-linked product of an amphiphilic cardanol derivative represented by the following chemical formula 1: [Chemical formula 1] in, R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl; and R2 represents at least one selected from the group consisting of a C1-C10 alkyl group, a C2-C10 alkenyl group, and a C2-C10 alkynyl group, and has a structure substituted with at least one anionic functional group.
2. The sulfur-carbon composite material according to claim 1, wherein: The surface of the sulfur-carbon composite material exhibits a zeta potential satisfying the following formula 1: [Formula 1] -60 mV≤ζ≤0 mV.
3. The sulfur-carbon composite material according to claim 1, wherein: At least one of R1 and R2 in the amphiphilic cardanol derivative has a structure including at least one unsaturated bond between carbon atoms.
4. The sulfur-carbon composite material according to claim 1, wherein R2 represents -(CH x ) n Q (wherein x=0, 1 or 2, n is an integer of 1-10, and Q is an anionic functional group).
5. The sulfur-carbon composite material according to claim 1, wherein: The anionic functional group comprises at least one functional group selected from the following: - 、-SO3 - 、-COO - 、-SO4 2- and its conjugate acid.
6. The sulfur-carbon composite material according to claim 1, wherein: The anionic functional group contained in R2 further includes at least one of an alkali metal ion and an alkaline earth metal ion as a cation.
7. The sulfur-carbon composite material according to claim 1, wherein: The cross-linking degree of the cross-linked product of the amphiphilic cardanol derivative is 15%-45% as determined by the following formula 2: [Formula 2] Cross-linking degree (%)=(carbon unsaturation degree of the cross-linked product of the amphiphilic cardanol derivative / carbon unsaturation degree of the amphiphilic cardanol derivative)×100.
8. The sulfur-carbon composite material according to claim 1, wherein: R1 in the amphiphilic cardanol derivative has at least one structure selected from the following Chemical Formulas 2 to 5: [Chemical formula 2] [Chemical formula 3] [Chemical formula 4] [Chemical formula 5] 。 9. The sulfur-carbon composite material according to claim 8, wherein: The amphiphilic cardanol derivative comprises: 1 part by weight to 10 parts by weight of wherein R1 represents the structure of Chemical Formula 2, 40 parts by weight to 70 parts by weight of wherein R1 represents the structure of Chemical Formula 3, 5 parts by weight to 25 parts by weight of wherein R1 represents the structure of Chemical Formula 4, and 25 parts by weight to 40 parts by weight of the structure wherein R1 represents Chemical Formula 5.
10. The sulfur-carbon composite material according to claim 1, wherein: The porous carbonaceous substrate comprises: carbon black, carbon fiber, carbon nanotube (CNT), graphene, graphene oxide (GO), reduced graphene oxide (rGO), graphite, graphite nanofiber (GNF), carbon nanofiber (CNF), activated carbon fiber (ACF), natural graphite, artificial graphite, expanded graphite, activated carbon, fullerene or two or more thereof.
11. The sulfur-carbon composite material according to claim 1, wherein: The sulfur-containing compounds include inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 2≤x≤8), a disulfide compound or a mixture of two or more thereof.
12. The sulfur-carbon composite material according to claim 1, wherein: The total content of the cross-linked product of the amphiphilic cardanol derivative is 0.1 wt % to 10 wt % based on the total weight of the sulfur-carbon composite material.
13. The sulfur-carbon composite material according to claim 11, wherein: The total content of the cross-linked product of the amphiphilic cardanol derivative is 0.1 wt % to 1 wt % based on the total weight of the sulfur-carbon composite material.
14. A method for preparing a sulfur-carbon composite material, the method comprising the following steps: preparing an uncoated sulfur-carbon composite material, the uncoated sulfur-carbon composite material comprising: a porous carbonaceous substrate; and a sulfur-containing compound supported on at least one of an outer surface of the porous carbonaceous substrate and an inner surface of a pore of the porous carbonaceous substrate; coating the surface of the uncoated sulfur-carbon composite material entirely or at least partially with an amphiphilic cardanol derivative; and Cross-linking at least a portion of the coated amphiphilic cardanol derivative to obtain a sulfur-carbon composite material whose surface is fully or partially coated with a cross-linked product of the amphiphilic cardanol derivative, in, The amphiphilic cardanol derivative is represented by the following chemical formula 1: [Chemical formula 1] wherein R1 represents at least one selected from C10-C50 alkyl, C10-C50 alkenyl and C10-C50 alkynyl; and R2 represents at least one selected from the group consisting of a C1-C10 alkyl group, a C2-C10 alkenyl group, and a C2-C10 alkynyl group, and has a structure substituted with at least one anionic functional group.
15. The method for preparing a sulfur-carbon composite material according to claim 14, further comprising the step of preparing the amphiphilic cardanol derivative by alkylation of a cardanol derivative represented by the following Chemical Formula 6: [Chemical formula 6] in, R1 represents at least one selected from the group consisting of a C10-C50 alkyl group, a C10-C50 alkenyl group, and a C10-C50 alkynyl group.
16. A positive electrode for a lithium-sulfur battery, the positive electrode for a lithium-sulfur battery comprising: The sulfur-carbon composite material according to any one of claims 1 to 13; and Binder polymer.
17. A lithium-sulfur battery, comprising a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte. in, The positive electrode includes the positive electrode according to claim 16.